Aspect of Asset Behavior in Continuous Time Macroeconomic Models - Douglas D. Purvis (Queen's University, Department of Economics, 1972)
It is the purpose of the present paper to consider, in the context of a continuous time macroeconomic model, how the explicit consideration of the existence of adjustment costs(including foregone consumption) which preclude instantaneous changes in the level of certain stock variables modifies our interpretation of the 'conventional' macro-economic analyses. In the following section of the paper, we consider the interpretations of asset demand functions and of the traditional stock constraint. Attention is given to the implications of different possible specifications of adjustment costs-in particular, two specifications which might be thought to correspond to the theory of the individual asset holder and to the theory of the economy as a whole will be treated. The distinction is drawn between positions of short run, or transitory, equilibrium characterized by flow equilibrium in assets, and positions of long run, or full, equilibrium characterized in addition by(long-run) stock equilibrium. Implications for the specification of asset demand functions are considered. Finally, implications for the dynamics of adjustment from one position of full equilibrium to another will be derived.
Keywords: 330